2019
DOI: 10.2485/jhtb.28.129
|View full text |Cite
|
Sign up to set email alerts
|

Carbonated Soft Drink-Soaking Change the Crystallographic Properties of Human Tooth Enamel -A Micro-XRD Study

Abstract: To elucidate the crystallo-chemical reaction between the enamel and carbonated soft drink, a micro-X-ray diffraction analysis (micro-XRD) was conducted using the human tooth sections soaked in the drink (Sprite ®) for 1 and 7 days. In this study, 4 typically and heavily dissolved teeth were selected from 20 teeth, and the divergence of the crystallographic properties of the enamel was analyzed. All of the untreated human tooth enamels exhibited only the apatitic XRD patterns. We confirmed that the carbonated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Our previous studies have shown that the composition of biogenic apatite in human enamel varies among individuals. Furthermore, the enamel of individual specimens clearly shows characteristic differences, indicating enamel diversity (9) . Heating also amplified enamel component fluctuations.…”
mentioning
confidence: 99%
“…Our previous studies have shown that the composition of biogenic apatite in human enamel varies among individuals. Furthermore, the enamel of individual specimens clearly shows characteristic differences, indicating enamel diversity (9) . Heating also amplified enamel component fluctuations.…”
mentioning
confidence: 99%